A Life Satisfaction of A Dual Role Woman - Ria, Yanah; Palupiningdyah, Palupiningdyah (Universitas Negeri Semarang, 2020)
This study aims to Determine the effect of work family conflict and work engagement on life satisfaction through work life balance as a mediating variable of study in female nurses at RSI who are married. The type and design of research used in this study is quantitative research. Sampling in this study using proportional sampling sampling technique and Obtained sample size that must be used is 118 female nurses who are married, the analytical method used is the instrument test (validity and reliability), classic assumption test, and hypothesis testing with the application of SPSS 23. Data collection methods using interviews, questionnaires, and literature studies. The results of this study indicate that five hypotheses were accepted, and two hypotheses were rejected. So it can be seen that work family conflict has a negative and not significant effect on life satisfaction. Work engagement has a positive and significant effect on life satisfaction. Work family conflict has a negative and significant effect on work life balance. Work engagement has a positive and significant effect on work life balance. Whereas the work life balance is only Able to mediate the relationship between work engagement and life satisfaction.Suggestions for future research are to develop other variables that can mediate the relationship of work family conflict in the life satisfaction of female nurses, for example social support. While the advice for the hospital is to reduce the activities that make-female nurses so tired, and provide time off when it is Necessary to reduce conflicts that occur